Pames, Jonaces, and Franciscans in the Sierra Gorda: Mecos and missionaries - Jackson, Robert Howard (Cambridge Scholars Publishing, 2017)
In the mid-sixteenth century, the Spanish faced a prolonged conflict in Mexico known as the Chichimeca War (1550-1600) beyond the porous cultural frontier between the sedentary indigenous populations of central Mexico and the bands of nomadic hunters and gatherers collectively known by the derogatory Náhuatl term "Chichimeca" or "Mecos". Franciscan, Dominican, and Augustinian missionaries developed methods and an organizational scheme to evangelize the sedentary populations of central Mexico, but this did not work well beyond the Chichimeca frontier where missions often proved to be ephemeral